Exploring Variability in Hypertension Management: Bridging the Gap Between Guidelines and Clinical Practice in Tripoli, Libya - Elreyani, Nasruddin; Alzintanyِ, Masarra; Almojahed , Alkhansa (AlQalam Journal of Medical and Applied Sciences, 2025)
Hypertension is a leading cardiovascular risk factor worldwide. Despite well-established guidelines from ESC/ESH, AHA, and NYHA, significant variability exists in clinical management, potentially affecting patient outcomes. Clinical pharmacists have a pivotal role in enhancing guideline adherence and supporting individualized therapy. To evaluate physicians’ adherence to hypertension guidelines, investigate factors influencing treatment decisions, and highlight the contribution of clinical pharmacists in bridging gaps between guideline recommendations and real-world practice. A prospective cross-sectional questionnaire-based study was conducted from June to December 2024 among 80 physicians in Tripoli, Libya, across multiple healthcare centers. Data collected included demographics, guideline adherence, diagnostic and treatment practices. Statistical analyses included descriptive statistics, chi-square/Fisher-Freeman tests, Spearman’s correlation, and ROC analysis to identify associations and predictors of adherence. Participants were predominantly hospital-based, with 48.8% holding bachelor’s degrees. Only 31.2% of physicians adhered strictly to hypertension guidelines. Internationally recognized guidelines were the most frequently used reference (67.5%), and 53.8% employed ambulatory blood pressure monitoring (ABPM) for diagnosis. Adherence was significantly associated with patient follow-up frequency (p<0.001) and appropriate combination therapy decisions (p=0.004). Factors contributing to treatment variability included resource limitations, workload, and reliance on personal experience. Clinical pharmacists were identified as essential in supporting guideline implementation, optimizing therapy, and promoting patient-centered care. Considerable variability exists in hypertension management among physicians in Tripoli. Integrating clinical pharmacists into the healthcare team can improve adherence to evidence-based guidelines, facilitate appropriate treatment decisions, and enhance patient outcomes.